Ground Motion Simulations of the SW Iberia Margin: Rupture Directivity and Earth Structure Effects. - Bezzeghoud, M. (2011)
Abstract In this study, we focus on the region between Gorringe Bank and the Horseshoe Fault located in the SW Iberia margin, which is believed to be the site of the great 1755 earthquake. We model ground motions using an extended source located near the Horseshoe scarp to generate synthetic waveforms using a wave propagation code, based on the finite-difference method. We compare the simulated waveforms, for the Algarve Basin and the Lower Tagus Valley Basin (Portugal), using a 3-D velocity model down to the Moho discontinuity with a simple 1-D layered model. The radiated wave field is very sensitive to the velocity model and a small number of source parameters, in particular, the rupture directivity. The rupture directivity, the strike direction and the fault dimensions are critical to the azimuthal distribution of the maximum amplitude oscillations. We show that the use of a stratified 1-D model is inappropriate in SW Iberia, where sources are located in the oceanic domain and receivers in the continental domain. The crustal structure varies dramatically along the ray paths, with large-scale heterogeneities of low or high velocities. Moreover, combined with the geometric limitations inherent to the region, a strong trade-off between several parameters is often observed; this is particularly critical when studying moderate magnitude earthquakes (M < 6), which constitute the bulk of the seismic catalogue in SW Iberia.